2001
DOI: 10.1046/j.1442-2050.2001.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Handsewn or stapled esophagogastric anastomoses after esophagectomy for cancer: meta-analysis of randomized controlled trials

Abstract: Gastric transposition with esophagogastric anastomosis is a common method of reconstruction after esophagectomy for cancer. The anastomosis can be fashioned using a handsewn or stapled technique. The choice of anastomotic technique is often debated but there is little evidence to support the use of one method over the other. We performed a meta-analysis of randomized controlled trials (RCTs) to determine the effect of esophagogastric anastomotic method (handsewn or circular stapled) on patient outcomes. Medlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 21 publications
0
74
1
9
Order By: Relevance
“…A sutura mecânica invertida é dupla e faz com que haja melhor coaptação da linha de anastomose, o que pode explicar a menor incidência de fístula com esse tipo de sutura como tem sido demonstrado por várias séries 3,16,24 . Em revisão recente de vários trabalhos da literatura relacionada à deiscência da anastomose esofagogástrica cervical, Chunwei F., et al 8 , demonstraram que essa complicação foi significantemente maior quando foi realizada sutura manual em 263 pacientes, com 18,7 % de deiscência anastomótica, quando comparado com a sutura mecânica em 195 pacientes, com 8,2%.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A sutura mecânica invertida é dupla e faz com que haja melhor coaptação da linha de anastomose, o que pode explicar a menor incidência de fístula com esse tipo de sutura como tem sido demonstrado por várias séries 3,16,24 . Em revisão recente de vários trabalhos da literatura relacionada à deiscência da anastomose esofagogástrica cervical, Chunwei F., et al 8 , demonstraram que essa complicação foi significantemente maior quando foi realizada sutura manual em 263 pacientes, com 18,7 % de deiscência anastomótica, quando comparado com a sutura mecânica em 195 pacientes, com 8,2%.…”
Section: Discussionunclassified
“…Por ser o esôfago cervical o segmento que apresenta a maior incidência de deiscência anastomótica, vários autores preconizam a sutura mecânica a este nível, devida as vantagens que ela oferece 5,8,11,12,22,24,28 . Nesse pressuposto, pode-se utilizar a sutura mecânica com o tubo gástrico isoperistáltico mesmo no intuito paliativo para tentar minimizar a deiscência anastomótica e oferecer qualidade de vida mais satisfatória.…”
Section: Introductionunclassified
“…Both HS and CS methods are fashioned in conducting the esophagogastric anastomosis in the past two decades [37]. Several retrospective studies [6,22,38], as well as firm evidence from relevant RCTs, have showed that both of them were safe. Meanwhile, with higher costs [17,34] and being less time-consuming [25,35], the CS method was associated with higher stricture rate related to high mortality.…”
Section: Summary Of the Current Researchesmentioning
confidence: 99%
“…Staple with a circular stapler (CS) is regarded as a safe alternative to manual suturing in colonic, rectal [4], and gastric anastomosis [5], as well as esophagogastric anastomosis [6]. With the development of surgical techniques, many advances have been applied to the surgery of esophageal cancer in the past decade [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation